Deep Learning : Sebuah Pendekatan untuk Pembelajaran Bermakna - Fatmawaty Fatmawaty (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to examine the Deep Learning approach as a strategy for creating meaningful learning. The research employs a literature review method, utilizing a systematic approach to collect, analyze, and synthesize information from various written sources such as reference books, scientific articles, research reports, and other relevant documents. Its main focus is to understand and evaluate existing theories or research findings in order to answer the research questions without conducting field data collection. The research procedure includes problem formulation, searching for relevant literature, selecting valid and reliable sources, recording important data, conducting critical content analysis, and drawing conclusions. The findings indicate that the Deep Learning approach plays a significant role in fostering meaningful learning and supports effective pedagogical practices. Meaningful learning encourages the development of higher-order thinking skills such as critical and analytical thinking. When students engage in meaningful learning processes, they are better equipped to develop future-relevant competencies and enhance long-term cognitive development. Many education experts today believe that meaningful learning promotes deep understanding, long-term memory retention, and the ability to apply knowledge in real-life situations. This aligns with David Ausubel’s theory, which emphasizes that learning becomes meaningful when new information is connected to relevant concepts already present in an individual’s cognitive structure.